72.3k views
3 votes
Solve for the equation, show all your work: 6x(x + 1) = -2(3x + 9)

User Kinda
by
5.5k points

2 Answers

3 votes

Answer:

There are no real solutions

Explanation:

6x(x+1)=-2(3x+9)

divide both sides by 2

3x*(x+1)= -(3x+9)

distibute

3x^2 + 3x= -3x-9

move variable and change sign

3x^2+3x+3x=-9

collect like terms

3x^2+6x= -9

divide both sides by 3

x^2 +2x=-3

add 1^2 to both sides of the equation

x^2+2x+1^2=-3+1^2

factor and simplify

(x+1)^2= -2

solve for x

(This statement is false for any value of x because the power function with an even exponent is always positive or 0)

User John Anderson
by
5.5k points
2 votes

Answer:

x = 9

⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕⊕

Answer x = 9

User Andrei Aulaska
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.